EFFECTS OF IDENTIFYING TRANSFUSIONAL INCIDENTS BY ACTIVE SEARCHING AT A TERTIARY HOSPITAL - Bedaque, Henrique; Soares, Rodolfo Daniel de Almeida; Brito, Carolina Lemos de; Revoredo, Gabriela Lia de Aquino (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Objective: The present study aims to analyze implementation consequences on active search for incidents related to blood transfusion at Onofre Lopes University Hospital (HUOL) and establish a blood transfusion profile in this facility. Methods: Blood transfusion and TIs registered on Hemotherapy Core at HUOL were counted through SPSS 20, comparing IT/1000 blood transfusion averages between 2012 and 2014. T Test of Student was used to compare data and chi-square (X²) and relative risk calculation to associate the use of blood components and risk to develop TI. Results: An increase of TI numbers at HUOL was shown by active searching and its equivalence to reference French and Brazilian services, liked to ANVISA sentinel network. Thus, there was a change in the average rate from 1.86 TI/1000 blood transfusions in 2012 to 5.36 TI/1000 blood transfusions in 2013 and 5.86 TI/1000 in 2014 (p = 0.001). It was also observed that the red blood cell concentrate is the fraction with the highest risk of occurrence of TIs (p = 0.003) and the greatest chance of causing any type of TI in relation to the other blood products, RR = 1.848 (95% CI; 1.042 - 3.266). It was also seen that the infusion of platelet concentrate is related to the allergic reaction (p <0.01), and greater risk compared to other blood components, RR = 2.746 (95% CI; 1.477 - 5.107). Conclusion: This study demonstrates active Hemovigilance importance on Tis subnotifications decrease.